2020
DOI: 10.1016/j.jcbs.2020.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the impact of carer stressors and psychological inflexibility on depression and anxiety in family carers of people with dementia

Abstract: This study aimed to explore the impact of carer stressors (neuropsychiatric symptoms of dementia, level of independence in activities of daily living, hours of caring per week), demographic factors (carer age, relationship with the person with dementia, dementia type, dementia severity, number of years since diagnosis and cohabitation status) and psychological inflexibility on depression and anxiety in family carers of people with dementia. Eighty-nine family carers with a mean age of 69.13 years old completed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
23
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 48 publications
3
23
0
1
Order By: Relevance
“…Evidence shows that ACT is effective in improving psychological flexibility and mental health outcomes in clinical and non-clinical youth and adult populations (see the review of meta-analyses, [ 58 ]). In other research, psychological flexibility was also associated with decreases in stress in adult carers [ 60 , 61 ]. A meta-analysis of ACT interventions for adult family carers found that ACT had moderate effects on depression and quality of life, small effects on anxiety, and small to moderate effects on stress [ 61 ].…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Evidence shows that ACT is effective in improving psychological flexibility and mental health outcomes in clinical and non-clinical youth and adult populations (see the review of meta-analyses, [ 58 ]). In other research, psychological flexibility was also associated with decreases in stress in adult carers [ 60 , 61 ]. A meta-analysis of ACT interventions for adult family carers found that ACT had moderate effects on depression and quality of life, small effects on anxiety, and small to moderate effects on stress [ 61 ].…”
Section: Discussionmentioning
confidence: 81%
“…Results from the present study suggested that the six ACT processes used to foster psychological flexibility could be tailored to help youth effectively balance their caregiving responsibilities in relation to other valued pursuits and manage their perceptions of care-giving stress [ 60 ]. Evidence shows that ACT is effective in improving psychological flexibility and mental health outcomes in clinical and non-clinical youth and adult populations (see the review of meta-analyses, [ 58 ]).…”
Section: Discussionmentioning
confidence: 99%
“…Equally, Romero-Moreno et al (2016) demonstrated that psychological inflexibility as assessed by the Acceptance and Action Questionnaire (AAQ-II) was significantly correlated with higher levels of depression and anxiety, and that, experiential avoidance, rumination, and satisfaction with leisure significantly mediated the association between stressors and anxiety among family caregivers of people with dementia. Further, the findings of Kishita et al (2020) suggested that psychological inflexibility as measured by AAQ-II was the only significant predictor of anxiety in family caregivers of people with dementia. These studies, using the AAQ-II, a generic measure of psychological inflexibility, suggest that psychological inflexibility plays an important role in caregiver distress.…”
Section: Introductionmentioning
confidence: 97%
“…Despite the high prevalence of depression and anxiety in family carers of people with dementia (Collins & Kishita, 2020;Kaddour & Kishita, 2020), many family carers have limited access to face-to-face psychological support due to various challenges. For example, family carers often spend long hours providing care, which can be equivalent to a full-time job (Jutkowitz et al, 2019;Kishita et al, 2020;Wolff et al, 2017) and can exceed 100 hours per week (NHS Digital, 2017) making it difficult for them to leave their house, particularly if they are unable to identify other family members or friends to provide care while they attend in-person support. Family carers living in rural areas face further difficulties due to the lack of local services, specialist providers and public transport (Alzheimer's Society, 2018;Samia et al, 2014).…”
Section: Introductionmentioning
confidence: 99%